Coalitional differential three-person game - Skėrus, S.; Jačiauskas, J. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:С. Л. Скерус, И. П. Ячяускас. Коалиционная дифференциальная игра трех лицS. Skėrus, I. Jačiauskas. Koalicinis diferencialinis trijų asmenų lošimas